2017
DOI: 10.1371/journal.pone.0170431
|View full text |Cite
|
Sign up to set email alerts
|

Association of microRNA-33a Molecular Signature with Non-Small Cell Lung Cancer Diagnosis and Prognosis after Chemotherapy

Abstract: ObjectiveThis study aims to explore the expression pattern and prognostic significance of miR-33a in non-small cell lung cancer (NSCLC) treated with adjuvant chemotherapy.MethodsMiR-33aexpression in NSCLC was analyzed in silico using the GEO database and was subsequently confirmed by quantitative RT-PCR in 147 NSCLC biopsies. Among these, 32 of these biopsies were paired with adjacent non-neoplastic tissues. The survival analysis of NSCLC by Kaplan-Meier estimates was stratified based on miR-33a expression. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…These affects are mainly due to the regulation of messenger RNA (mRNA) by miRNA . In addition, various types of miRNAs display different levels of expression in specific types of malignancies . Therefore, the mRNA and miRNA data of a patient with LUSC samples in the TCGA database were used to find new biomarkers in our study.…”
Section: Introductionmentioning
confidence: 99%
“…These affects are mainly due to the regulation of messenger RNA (mRNA) by miRNA . In addition, various types of miRNAs display different levels of expression in specific types of malignancies . Therefore, the mRNA and miRNA data of a patient with LUSC samples in the TCGA database were used to find new biomarkers in our study.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained the highest AUC values (viz., 0.95 for SVM, 0.955 for RF, 0.955 for PAM) for our resultant gene signature estimated by our proposed method, De-MoS. On the other hand, for the gene signature obtained by Li et al (2017) [6], the corresponding AUC values across these three classifiers were 0.535 for SVM, 0.5625 for RF and 0.585 for PAM, whereas for the gene signature found by Li et al (2018) [28], those values were 0.535 for SVM, 0.5625 for RF and 0.585 for PAM. Another gene signature estimated by Huang et al (2011) [29], the AUC values for SVM, RF and PAM classifiers were 0.83, 0.66 and 0.75, respectively.…”
Section: Resultsmentioning
confidence: 67%
“…Gene signatures might be targeted by various miRNAs, which are non-coding RNAs (approximately 18-25 nucleotides long) that participate in the post-transcriptional regulation of gene expression [5]. These miRNAs are abnormally expressed in various malignancies as tumor suppressors or oncogenes [6]. They regulate various processes in carcinogenesis such as metastasis [7] and cell proliferation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that miRNAs regulated various carcinogenesis processes including cell maturation, cell proliferation, migration, invasion, autophagy, apoptosis, and metastasis [9]. Therefore, this suggests that miRNAs can be potential noninvasive biomarkers for cancer [8] and have a large potential to serve as promising markers in the diagnosis, prognosis, and personalized targeted therapies [9,10].…”
Section: Introductionmentioning
confidence: 99%